2019
DOI: 10.1155/2019/1730452
|View full text |Cite
|
Sign up to set email alerts
|

Antitrypanosomal Effects of Zanthoxylum zanthoxyloides (Lam.) Zepern. & Timler Extracts on African Trypanosomes

Abstract: African trypanosomiasis is a disease caused by the parasitic protozoa of the Trypanosoma genus. Despite several efforts at chemotherapeutic interventions, the disease poses serious health and economic concerns to humans and livestock of many sub-Saharan African countries. Zanthoxylum zanthoxyloides (Lam.) Zepern. & Timler (Z. zanthoxyloides LZT) is a plant species of important phytochemical and pharmacological relevance in the subtropical zones of the African continent. However, the mechanisms of its antit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
17
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 10 publications
(17 citation statements)
references
References 38 publications
0
17
0
Order By: Relevance
“…Chromatographic, spectrometric, and spectroscopic analyses were performed by following the procedures and conditions employed in our previous studies [ 14 , 26 ]. Analytical normal phase silica-coated thin layer chromatography (TLC) was run on both Kupchan and gravity column fractions to estimate the levels of polarity and purity of all fractions, and to determine the appropriate solvent systems for silica gel gravity column chromatography.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Chromatographic, spectrometric, and spectroscopic analyses were performed by following the procedures and conditions employed in our previous studies [ 14 , 26 ]. Analytical normal phase silica-coated thin layer chromatography (TLC) was run on both Kupchan and gravity column fractions to estimate the levels of polarity and purity of all fractions, and to determine the appropriate solvent systems for silica gel gravity column chromatography.…”
Section: Methodsmentioning
confidence: 99%
“…Effect of compounds on parasite morphology was investigated microscopically by following the same conditions and protocols described in our previous study [ 26 ]. T. b. brucei cells were treated with compounds at the EC 50 values for 24 h. Paraformaldehyde (final concentration of 4%) was used as the fixative and DAPI was used for the visualization of the nucleus and kinetoplast.…”
Section: Methodsmentioning
confidence: 99%
“…In Nigeria and Ghana, roots, stem and leaves of Z. zanthoxyloides are used in treating trypanosomiasis ( Mann et al, 2011 ). When cultured with the root extract, the viability of T. brucei was demonstrated to be suppressed (IC 50 = 3.41 μg/ ml) by induction of apoptosis and cell cycle arrest at G0/G1 phase ( Dofuor et al, 2019 ). Subsequent investigation by the same group resulted in the isolation of an alkaloid, skimmianine, and an oxylipin, 9-oxo-10,12-octadecadienoic acid, from Z. zanthoxyloides root as the cytotoxic principles against T. brucei (GUTat 3.1 strains; EC 50 values of 1.7 and 1.2 µM, respectively) ( Dofuor et al, 2020 ).…”
Section: Zanthoxylum Species As Potential Source Of Anti-parasitic Agentsmentioning
confidence: 99%
“…Previously, the anti-inflammatory and gastroprotective effects of Zanthoxylum zanthoxyloides were demonstrated [9,11,12]. On the basis of these reports, many studies have investigated some bioactivities of Zanthoxylum zanthoxyloides including antiplasmodial [13], antitrypanosomal [14], antimalarial [15], antihelminthic [16], antisickling [17], and diversity of the genus [18]. Also, it was shown that Zanthoxylum zanthoxyloides contain diverse phytocompounds including flavonoids, tannins, coumarins, fluoroquinoline, oxylipin, aromatic compounds, acridone alkaloids, fluoride, and zantholic acid [19][20][21][22][23][24][25].…”
Section: Introductionmentioning
confidence: 99%